THE INFLUENCE OF RELATIONSHIP MARKETING TOWARDS CUSTOMER RETENTION EFFORTS ON CULINARY SEAFOOD CRAB'S NEST RESTAURANT IN THE CITY OF JAMBI - Jamal Jamal; Ade Titi Nifita; Garry Yuasa Rosyid (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
The purpose of this study was to study the relationship of marketing to customer retention in seafood food companies in crabs in the city of Jambi, as well as identify things that need to be considered in improving customer retention. The data in this study used a survey method using a questionnaire given to 105 respondents. The data were analyzed using multiple linear regression techniques. The results of statistical tests simultaneously, dimensions, commitment, communication, and handling were significantly positive and significant for customer retention, with an influence value (R2) of 54.5%. The results showed that partially, dimensions, commitment, and communication had a positive and significant effect on customer retention, while the handling dimension was not significant to customer retention. Thus, efforts are needed to improve the quality of handling speed in order to increase customer retention in the crab seafood restaurant culinary business in Jambi City.